Captive environmental change and induction of natural breeding and egg‐laying in ploughshare tortoises (Astrochelys yniphora). Issue 3 (26th February 2021) - Kiryu, Daisuke; Otaki, Yusuke; Kido, Nobuhide; Hara, Kumiko
Abstract: The ploughshare tortoise ( Astrochelys yniphora ) is an endangered species. It is important to increase the number of tortoises in the wild and captivity; however, breeding in captivity, especially outside of the natural habitat area, has been unsuccessful worldwide. As a result of an emergency rescue due to a violation of the Act of Conservation of Endangered Species of Wild Fauna and Flora, Nogeyama Zoological Gardens (Yokohama, Japan) has housed ploughshare tortoises, and a natural breeding trial started in 2011. In this case, the captive environment in Nogeyama, especially room temperature and humidity, imitated the environment in the natural habitat of northwest Madagascar. The maximum temperature during the day was 30.8–32.5°C throughout the year, but the minimum temperature was 24°C during December and January, representing the rainy season, and 17°C during July, representing the dry season. The humidity was adjusted and the room was not humidified between November and February (dry season) but was humidified by sprinkling water once every few days in March and daily between April and October (rainy season). Natural breeding and egg‐laying were observed 1 year after the captive environmental change. Three neonates were hatched from nine eggs in 3 years after the beginning of the breeding program. This study showed that for natural breeding of the ploughshare tortoises, it is important to adjust the temperature and humidity of the captive environment to imitate the temperature and humidity of the natural habitat. Abstract : The male ploughshare tortoise mounted on the female for the breeding. ResearchHighlight: It is important for natural breeding of the ploughshare tortoises to adjust the temperature and humidity of the captive environment to imitate the temperature and humidity of the natural habitat. Natural breeding and egg‐laying were observed and three neonates were hatched from nine eggs in 3 years after the beginning of the breeding program.